2020
DOI: 10.1080/09640568.2020.1828840
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nature documentaries on public environmental preferences and willingness to pay: entropy balancing and the blue planet II effect

Abstract: In this study the discrete choice experiment approach was employed in a survey of the Scottish general public to analyse how respondents make trade-offs between blue growth potential and marine ecosystem service delivery associated with the Mingulay cold water reef complex.Results indicate a higher willingness to pay for management options associated with the highest possible levels of marine litter control followed by the highest possible levels of fish health.Using entropy balancing, a multivariate reweighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Average causal effect values for all species and conservation themes regardless of significance can be seen in Figure shows that although they did record increases in page views after the broadcast of Blue Planet II episodes, these topics were already receiving heightened public attention in the lead up to the show, explaining the non-significant results of the causal impact analysis for these articles. This calls into question whether the show did indeed create the 'Blue Planet effect' it is often attributed (Hynes et al, 2020;Males & Van Aelst, 2021), or if it was broadcast in an already plastics-conscious moment, riding this wave and perhaps giving it increased vigour. For example, policy measures to combat plastic pollution were linked in the UK media to the then Environmental Minister Michael Gove's 'haunted' reaction to scenes in Blue Planet II (Aitchison et al, 2021;Rawlinson, 2017), however, measures such as plastic bottle deposit schemes were already in discussion weeks before Blue Planet II aired (Carrington, 2017a(Carrington, , 2017b.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Average causal effect values for all species and conservation themes regardless of significance can be seen in Figure shows that although they did record increases in page views after the broadcast of Blue Planet II episodes, these topics were already receiving heightened public attention in the lead up to the show, explaining the non-significant results of the causal impact analysis for these articles. This calls into question whether the show did indeed create the 'Blue Planet effect' it is often attributed (Hynes et al, 2020;Males & Van Aelst, 2021), or if it was broadcast in an already plastics-conscious moment, riding this wave and perhaps giving it increased vigour. For example, policy measures to combat plastic pollution were linked in the UK media to the then Environmental Minister Michael Gove's 'haunted' reaction to scenes in Blue Planet II (Aitchison et al, 2021;Rawlinson, 2017), however, measures such as plastic bottle deposit schemes were already in discussion weeks before Blue Planet II aired (Carrington, 2017a(Carrington, , 2017b.…”
Section: F I G U R Ementioning
confidence: 99%
“…Films and documentaries have long been suggested as an effective way to educate the general public about environmental issues (Erickson & Van Tubergen, 1972; Fortner & Lyon, 1985; Hofman & Hughes, 2018; Hynes et al, 2020). Natural history films are popular for their dramatic and beautiful depictions of the natural world.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the effects these changes might have on the public, some studies of students of varying ages have shown that increasing knowledge about animals increases positive attitudes towards those animals (83,84), including for sharks in particular (85). Television has the potential to drive conservation action or intention--for example, an increase in internet searches for conservation charities and sustainable practices were seen during and after the airing of Blue Planet II episodes (86,87). This does not mean that providing the public with positive representations of sharks, or accurate information about them, represents a solution to conservation problems or will necessarily generate interest or concern about them in itself (88)(89)(90).…”
Section: Recommendationsmentioning
confidence: 99%
“…Most simply, increasing richness (number) of species in a community can enhance visual complexity (Forsythe et al, 2011; Kaplan et al, 1972; Petrova et al, 2015) and the chances that species with favourable characteristics are included (Ulrich, 1983), intersecting strongly with empirical findings from the psychology of aesthetics where complexity and desirable traits can enhance aesthetic appeal (de Pinho et al, 2014; Palmer et al, 2013; Petrova et al, 2015). Species‐rich communities are also generally perceived to be more diverse, which may lead to positive aesthetic appraisals of communities through intrinsic existence values (Dallimer et al, 2012; Fisher et al, 2021; Schebella et al, 2019), particularly as public awareness of the importance of biodiversity in maintaining healthy ecosystems has increased over the past decade (Hynes et al, 2021; Shwartz et al, 2014; Wu et al, 2020). Species richness is, however, a coarse measure of community structure; visual complexity and diversity may be more discernible where species abundances have higher evenness (Graves et al, 2017; Tribot et al, 2019), or where species have more distinctive traits (characteristics; e.g.…”
Section: Introductionmentioning
confidence: 99%